Influencing Purchasing Decisions: The Interplay of Pricing and Product Quality for Garnier Facial Cleanser - Christianingrum, Christianingrum (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
The aim of this research is to determine the influence of price and product quality on purchase decisions for Garnier products. This study is a quantitative descriptive research using multiple linear regression analysis with a sample of 100 respondents from the Pangkalpinang city community, selected through purposive sampling. The research results indicate that price has a positive and significant effect on purchase decisions; product quality has a positive and significant effect on purchase decisions; and both price and product quality have a positive and significant effect on purchase decisions. The implications of this research are that companies need to understand that product quality and price are factors influencing purchase decisions. In this context, Garnier Company should develop more efficient and effective ways to compete with other companies, ensuring that purchase decisions are optimized. Keywords: Pricing; Product Quality; Buying Decision; Garnier; Pangkalpinang